Matched-Filter Based Frame-Start Detector Resilient to Frequency Offset - Lukac, J.; Kimmer, M.; Sykora, J. (Společnost pro radioelektronické inženýrství, 2025)
The article proposes a (phase-marginalized) frame-start detector resilient to frequency offset between the transmitter and the receiver. The detector is a slight modification of the standard detector that looks for a known sequence/preamble using the matched filter, respectively correlation of the received signal with the known sequence. The modification is that the original long sequence is divided into shorter ones; the magnitude or magnitude-squared of the output of matched-filters is taken and then appropriately added to get the final detector metric. The proposed detector is a low-cost alternative to the standard approach (joint estimation of frame timing and frequency offset), where we need as many matched-filters as the number of testing frequency offsets. We derive probability characteristics of the proposed detector that reflect its resilience to the frequency offset. The frequency resilience of the detector is proportional to the number of segments into which the preamble is divided.
Keywords: Frame synchronization; matched filtering; crosscorrelation; frequency offset